1996
DOI: 10.1074/jbc.271.25.15146
|View full text |Cite
|
Sign up to set email alerts
|

Long Exposure to High Glucose Concentration Impairs the Responsive Expression of γ-Glutamylcysteine Synthetase by Interleukin-1β and Tumor Necrosis Factor-α in Mouse Endothelial Cells

Abstract: To elucidate the pathological metabolism of glutathione synthesis in diabetic endothelial cells, we studied the expression of gamma-glutamylcysteine synthetase (gamma-GCS) using a mouse vascular endothelial cell line. Exposing normoglycemic endothelial cells to tumor necrosis factor-alpha (TNF-alpha) or interleukin-1beta (IL-1beta) increased the activity and the mRNA expression of gamma-GCS. The addition of inhibitors for nuclear factor kappaB (NF-kappaB) to the cells caused a loss of the gamma-GCS mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
1
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 43 publications
3
94
1
2
Order By: Relevance
“…A decrease in ␥-GCS mRNA expression and increase in DNA damage accompany this reduction. The decrease observed is in agreement with published results; Yoshida et al [15] found GSH levels 77% of controls in erythrocytes from diabetic patients, Urata et al [14] reported GSH levels 59% of normal glucose after 7 d in 22 mM glucose, and Tachi et al [25] found a decrease of 20% in HVSMC exposed to 27.5 mM glucose for 10 d. The depletion of GSH may be brought about through a variety of mechanisms, including an increased breakdown of GSH by ␥-glutamyltranspeptidase, an increased export of GSSG from the cell, or a reduction in de novo synthesis through reduced activity of ␥-GCS or availability of substrate. In human vascular smooth muscle cells, there is no significant difference in the rate of GSH efflux between cells exposed to high glucose compared to those in normal glucose [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A decrease in ␥-GCS mRNA expression and increase in DNA damage accompany this reduction. The decrease observed is in agreement with published results; Yoshida et al [15] found GSH levels 77% of controls in erythrocytes from diabetic patients, Urata et al [14] reported GSH levels 59% of normal glucose after 7 d in 22 mM glucose, and Tachi et al [25] found a decrease of 20% in HVSMC exposed to 27.5 mM glucose for 10 d. The depletion of GSH may be brought about through a variety of mechanisms, including an increased breakdown of GSH by ␥-glutamyltranspeptidase, an increased export of GSSG from the cell, or a reduction in de novo synthesis through reduced activity of ␥-GCS or availability of substrate. In human vascular smooth muscle cells, there is no significant difference in the rate of GSH efflux between cells exposed to high glucose compared to those in normal glucose [25].…”
Section: Discussionsupporting
confidence: 92%
“…Induction of ␥-GCS expression by oxidative stress is well established [38 -40], however exposure to high-glucose conditions decreases mRNA expression of both subunits in HVSMC. Urata et al [14] found that high concentrations of glucose in endothelial cells decreased GCS H mRNA expression and inhibited the stimulatory effect of IL-1␤ and TNF-␣ on induction of ␥-GCS. These results would suggest that glucose itself may have a direct effect on transcriptional regulation of both ␥-GCS subunits, but further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of GCL expression and activity has been studied in many other cell types, including mesangial and endothelial cells, but not the pancreatic islet. Long term exposure to high glucose levels decreases GCL expression in mesangial, retinal Muller, and endothelial cells, which results in a decrease in GSH levels (3)(4)(5). Long term exposure to high glucose conditions inhibits endothelial cells from responding to cytokine exposure with an increase in GCL expression and activity (3).…”
mentioning
confidence: 99%
“…8,12,13 Important cis-acting elements implicated in mediating the effect of oxidative stress on the promoter activity of the GCS subunits are antioxidant response element (ARE) and activator protein-1 (AP-1). 8,9,13 Nuclear factor-B (NF-B) may 10,14,15 or may not 9,16,17 regulate the heavy subunit. All studies have used cell lines transfected with recombinant GCS subunit promoterreporter gene constructs.…”
mentioning
confidence: 99%